EFFECTIVENESS OF SHOOTING BASKETBALL MODEL BASED OF DRILL AT FACULTY OF SPORT SCIENCE OF STATE UNIVERSITY OF MEDAN - Ibrahim Ibrahim; Moch. Asmawi; Iman Sulaiman (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
The purpose of this research is to get an overview of the implementation of basketball-based shooting learning on the students, to produce basketball shooting learning model, and to develop conceptual model and procedural model of shooting set shoot learning, jump shoot and basketball shoot layup and also to know effectiveness of efficient model. This research and development use Research & Development (R & D) development method from Borg and Gall. Group trials were conducted on second semester students who took basic basketball courses consisting of 4 classes totaling 120 people, 60 treatment groups and 60 as control groups with eight (8) meetings. The effectiveness test of the learning model uses shooting skill set shoot skill instruments, jump shoot and basketball shoot layup using portofolio (process assessment). Analysis of research data using t test with a significance level of 0.05. Data analysis for shoot shooting set obtained an average value of pretest 50.43 and posttest 75.57 t-count ratio and t-table -188.500 <1.67065, while the jump shoot obtained the average value of pretest 57.55 and posttest 82 , 85 t-count comparisons and t-tables -89,235 <1,67065 and for shoot layups, the average pretest score is 48,02 and posttest 73,17 t-count ratio and t-table -167,667 <1,67065, significance (2-tailed) 0.000 with a significance level of 0.05 then of the three H0 rejected. Based on the data analysis, it can be said that the set shoot, jump shoot and drill layup-based learning models for students are developed, effective and can improve the results of basketball shooting learning. Keywords: Effectiveness, Shooting Basketball Model, Based of Drill